Business Plan - Project Krishna - Saxena, Akansha; Gupta, Padam (2016)
Krishna ltd. is offering Jute products with exclusive designs & high quality. Jute Products are biodegradable and sustainable that creates consumer and societal value . They promote responsible consumption, and build an ethical fashion community.